Splenectomy in thalassemia - Firzli, Salim S. (The Turkish Journal of Pediatrics, 1962)
Twelve cases of thalassemia are presented with hematological observations before and after splenectomy. The author thinks that it is possible to detect hypersplenism in thalassemia even before the increased need of repeated transfusions makes it more evident.